Text Linguistics and Translation Studies: An Evaluation and Critique of the Text Linguistics and Translation Theory - Seyed Esmaeil Ghasemi Mousavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The text linguistics is one of that fields that has had a great impact on Translation Studies. In many definitions, translation has been defined as the replacement of a text in one language by a text in the target language, and a lot of researchers tried to use theories of text linguistics in translational investigation.  Accordingly, Yousof Noor Ewath tried in a communicative perspective to provide a short history of text linguistics and translation studies in his book "Elmonnas wa Nazariyat Al-Tarjomah" (The Text Linguistics and Translation Theory) and to explain the relationship between these two fields. So at the end of both book's two chapters, he has raised his theory of these fields and named it: (Nazariyat Al-Enziyahat) the shifts of theory. He recognizes three types of meaning in texts as Obligatory Meaning, Extended Meaning and Accessory Meaning, and based on the quantity of these different meanings in texts, it is divided into three types: Literary texts, non-literary text, and Fuzzy texts or Hybrid texts. In his opinion, with regard to this division and differences between each of these types, an appropriate translational strategy should be chosen.This paper with a descriptive-analytic method tries to review this book and  to analyze its appearance and content and to assess the degree of realization of book's goals That are, to write a text linguistic approached introduction to translation studies and also tried to study the compatibility of this work contents with Arabic language and literature field. The most important result of current study is as follows two reasons caused this book not to be a comprehensive introduction to the text linguistics and translation studies: first the book was published long time ago, and secondly, the book has not mentioned all the main tendencies of the two fields and lacks all the necessary topics related to curriculum which prevents this book from being considered as the main source of translation theory courses, but paying attention to the new ideas and a strong theoretical framework can present the  innovative research ideas and new thinking way about the translation process.